PENGARUH BEBAN KERJA FISIK TERHADAP KINERJA DENGAN STRESS KERJA SEBAGAI VARIABEL MEDIASI PADA PERAWAT DI RSUD MANDAU- DURI - Br. Silaban Efriyanti; Samsir Samsir; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
In the world's health care system, nurses have a very important role intreating and treating patients. The Mandau Duri Regional General Hospital is ahospital categorized as a type B hospital belonging to the Duri RegionalGovernment. Nurses at the Mandau Hospital must give their best performance.Behind a good performance, there will definitely be a physical workload andstress that follows. This study aims to determine the effect of physical workload onperformance with work stress as a mediating variable for nurses at Mandau DuriHospital. Primary data were collected with a questionnaire as an instrument. Totest the hypothesis using SEM with the help of the SMARTPLS applicationprogram. The population in this study includes all nurses who work in the ICUand IGD. Sampling technique using the census method, the sample of this studyamounted to 37 nurses. The results of the study indicate that: 1) there is anegative and significant influence between physical workload on the performanceof nurses in Mandau Hospital, 2) there is a positive and significant influencebetween physical workload on work stress in nurses at Mandau Hospital, 3) thereis an influence negatively and significantly between work stress on theperformance of nurses in Mandau Hospital, 4) there is a negative and significanteffect of physical workload on nurses' performance through work stress as amediating variable on nurses at Mandau Duri Hospital. Keywords: Physical Workload, Performance, and Job Stress